Measuring the Size of the Informal Economy: A Critical Review - George M. Georgiou
There has been a burgeoning number of studies attempting to measure the size of the ‘black’ economy. These are based on a variety of methodologies and provide a range of estimates, not just across countries but also within the same countries and often by the same author(s). This raises a number of issues: What is meant by the term ‘black’ economy? Is it an appropriate description? What, if any, is the theory underlying the estimates of informal economic activity? This paper examines these and other issues, and concludes that whilst the existence of what we prefer to call the ‘informal’ or ‘grey’ economy in most countries is incontrovertible, there is a lack of consensus on the appropriate methodology for estimating its size. More importantly, the large number of studies so far are simply exercises in measurement without theory, though we are sceptical that even with strong theoretical underpinnings it is possible to provide accurate estimates of a complicated web of informal activities.Informal, grey and black economy, tax evasion, criminal activities